La narrazione della memoria nell'opera di Primo Levi - Prosenc, Irena (Ars et humanitas, 2018)
Primo Levi, best known for his autobiographical texts narrating his internment in Auschwitz, analyses the notion of memory in numerous texts. Th e author observes that the unreliability of memory may undermine the verisimilitude of autobiographical narration. In his works memory has complex functions as an active process realised in the preservation and narration of memories. In If Th is Is a Man, Levi limits the object of his narration to what he personally witnessed and experienced. In Th e Truce he operates a selection of memories, whilst the essay Th e Drowned and the Saved is based on data provided by a substantial corpus of concentration camp literature. Th e purpose of Levi's memorial testimony is to restore certain annihilated aspects of the past and contribute towards the reconstruction of lost personal and collective identities. Furthermore, Levi realises that his narrative functions as some sort of artifi cial memory representing a protective barrier between the present and the traumatic past, whilst also keeping authentic memories at bay and blocking his immediate access to them.
Keywords: 20. st.; 20th century; autobiography; avtobiografija; extermination camps; genocid; genocide; Italian literature; italijanska književnost; koncentracijska taborišča; Levi, Primo; memory; spomin